Assessing the impact of landscape setting on the microclimate of outdoor spaces in hot-humid regions towards mitigating urban heat island - a preliminary investigation - Abu Bakar, Aniza; Mohamad, Amira Nadhirah; Sanusi, Aliyah Nur Zafirah (2013)
Urban Heat Island is a phenomenon where urban area is experiencing hotter environment compared to the surrounding rural area. Among others this is due to the modification on the environment following the development processes where urban area has significantly more hard surfaces (buildings, road network, paved surfaces, etc) compared to the surrounding rural area. These hard surfaces tend to absorb and store the heat from the solar radiation as well as the terrestrial radiation, before releasing it back to the environment leading to increasing air temperature. Countries located within the tropical region are greatly affected by this situation as they struggle more in trying to achieve their thermal comfort. Thus, this research seeks to investigate the influence of the landscape setting by looking into factors such as vegetation, ground surface materials and its built environment dimension and their impact on the outdoor microclimate. Outdoor environment seems to give certain impact to the indoor environment. Thus, studying these factors and their impact to the microclimate will provide scientific/empirical evidence that would be useful to guide the designer in preparing the landscape layout and selecting appropriate vegetation that could filter certain amount of solar radiation from reaching the ground surfaces towards cooler outdoor environment. This preliminary study seeks to quantify the impact of the landscape setting on the microclimate of the investigated spaces. The environmental variables to be considered are air temperature, relative humidity and wind environment, whereas elements of the landscape setting will include the ground surface material (paved/turfed), aspect of tress (location, quantity, quality of foliage density, and canopy diameter). The environmental parameters are recorded during the daytime as to see the effect in the presence of the solar radiation and also due to safety aspect of the equipment. Four spaces within the IIUM are investigated which represent generally two categories of landscape setting which are: shaded/green area and exposed area. The findings suggested that the landscape settings do influence the microclimate of outdoor spaces where high quantity of trees and big tree size seem to lower the air temperature readings. Turfed surfaces seem to demonstrate lower air temperature of its surroundings as a whole compared to tar-mac surfaces. The aspect of trees also seems to be significantly influence the microclimate.